DIGITAL INFORMATION ERA : STRATEGI PEMASARAN MUSEUM BENTENG VREDEBURG YOGYAKARTA MELALUI PENDEKATAN KOMUNIKASI PEMASARAN TERPADU - Astuti, Rini Linda Dwi; Ainurohmah, Dovianti; Novia; Qalban, Anas Azhimi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
Marketing plays a major role in the overall strategy of a company, through an integrated marketing communications strategy the Yogyakarta Fort Vredeburg Museum can introduce this tourist attraction to the wider community. This research aims to explain how the Fort Vredeburg Yogyakarta Museum uses an integrated marketing communications approach in its marketing strategy. This research has qualitative characteristics and adopts descriptive methods. The author uses data collection techniques through observation, interviews and literature study. Apart from that, the author uses a purposive sampling technique. In the data analysis process, researchers analyze the data, present the data, and draw conclusions. In this case, the steps to strengthen the marketing of the Yogyakarta Fort Vredeburg Museum, the initial stage is to carry out a SWOT analysis to help the effectiveness of the strategy and overcome challenges, then segmenting analysis starting from demographics, geography, psychographics, to behavior; targeting; and the next positioning is the marketing stage through advertising by means of promotion through events; Public relations involves good relations with visitors through tour guides and reception staff; sales promotion is carried out by holding concerts; personal sales involves collaboration with schools, employees who are friendly to visitors; as well as direct marketing in the form of websites that lead to responsive media. Thus, integrated marketing communications plays a major role in the marketing strategy of the Yogyakarta Fort Vredeburg Museum and contributes significantly to increasing the number of visitors